Implementation Of Management Information System (SIM) In Schools: A Case Study At SDN Wonogiri District - Dwi Estiningsih; Andi Arief Rifa’i (Mudir : Jurnal Manajemen Pendidikan, 2023)
The management approach in the digital era leads to the ability to design and utilize information system management (MIS). Information has become a resource in management, because it can be a tool that contributes positively to management activities. Urgency, cause of disaster and solutions to change decisions become an important part of the journey towards achieving goals in accordance with the basic conceptions of management. research methods used with qualitative descriptive data collection through observation, field and interviews. Data analysis is carried out by systematically compiling data obtained from interviews, field notes and documentation. Samples in the study of principals and school operators of SDN 1 Wonogiri, Wonogiri District, Wonogiri Regency, Central Java to get an overview of the implementation of information systems in management in elementary schools. Limited ability of operators because they are not special officers in their fields, lack of interest from educators and education staff towards mastery of renewable knowledge and technology and limited school funding to improve computer facilities with the latest specifications are obstacles to the implementation of management information systems in this school. Management information systems thinking helps develop thinking about the use of information systems as a new perspective in understanding management concepts and the role of system design in improving the decision-making process, In addition to concepts from several points of view, it is also described about the functions, components, properties, characteristics and types of information systems, levels of information systems and their use in organizations. The reality that information systems are an important component in organizational sustainability, especially to strengthen management performance to face challenges and prepare to win the competition. Collaborative steps with government and non-government/private institutions can be a solution to get support for the implementation of management information systems in realizing the school's vision and mission more effectively and efficiently